Risk factors associated with pulmonary arterial hypertension in Colombian patients with systemic sclerosis: Review of the literature (2008)
Objective. Considering the significant morbidity and mortality of pulmonary arterial hypertension (PAH) in patients with systemic sclerosis (SSc) and the lack of precise information on disease in Latin America, we investigated the clinical and laboratory characteristics associated with PAH in Colombian patients with SSc and review the literature. Methods. This multicenter study included patients followed at 5 rheumatology units that were systematically assessed using a pretested questionnaire on clinical and immunological variables, focusing on PAH. Conditional logistic regression was employed to assess association between PAH and specific clinical characteristics. A systematic review of the literature was performed through electronic databases. Results. Of a total of 349 patients with SSc, 61 (17%) met the criteria for PAH. Pulmonary fibrosis [adjusted odds ratio (AOR) 7.37, 95% CI 3.67-14.81, p less than 0.0001], microstomia (AOR 3.3, 95% CI 1.70-6.28, p less than 0.0001), gastroesophageal reflux (AOR 2.41, 95% CI 1.31-4.43, p = 0.005), dysphagia (AOR 2.7, 95% CI 1.49-4.77, p = 0.001), hyperpigmentation (AOR 2.15, 95% CI 1.11-4.16, p = 0.02), and hypopigmentation (AOR 2.4, 95% CI 1.26-4.64, p = 0.008) were the most prevalent clinical characteristics associated with PAH, while anemia (AOR 5.4, 95% CI 1.98-14.93, p = 0.001) was observed as the unique laboratory risk factor. Association between subtypes of SSc and PAH was not observed. Significant differences in both clinical and laboratory data were observed among different series. Conclusion. PAH may be a frequent complication of SSc in the Colombian population regardless of disease subtype. The identified clinical and laboratory risk factors might assist earlier diagnosis and guide decisions on therapeutic interventions on this critical complication of SSc. The reasons underlying the reported divergences among patients from different ethnicities are not fully understood, but it is most likely that both genetic and environmental factors are responsible for them.